Tanggung Jawab Notaris Terhadap Pembuatan Akta Peralihan Saham Perseroan Terbatas yang Menyuruh Menempatkan Keterangan Palsu dalam Data Pribadi - Nasution, Rahmat Faisal; Deni, Fitra; Herlina, Indah (Program Studi Hukum Universitas Pamulang, 2025)
In this digital era, database management for both individuals and corporations plays a crucial role in facilitating various transactions, whether for individuals or legal entities. Notaries are required to adapt to these advancements, as numerous transactions and documents are now conducted electronically and must be properly recorded to create authentic deeds while preventing misuse. According to Article 16, Paragraph 1 of the Notary Position Act (UUJN), notaries must prioritize the principle of prudence, particularly in managing personal data ownership. Negligence or intentional misconduct by a notary in drafting a General Meeting of Shareholders (GMS) Deed for Share Transfer without following the procedures stipulated in the Company Law (UUPT) and obtaining the data owner's consent may result in criminal liability for the notary. The foundation for a notary's role as a controller and manager of personal data is regulated under the UUJN and the Personal Data Protection Law. The method used to address this issue is a normative juridical approach, which involves legal, case, and conceptual analyses. This study examines the legal implications of personal data misuse by notaries in drafting deeds, as well as the necessary follow-up actions to prevent and address such cases. It is essential for every notary to adhere to established standards and procedures to uphold the integrity of the legal profession.